Kontribusi Islam Dalam Pengembangan Peradaban Dunia - Mardiah Astuti; Herlina, Herlina; Ibrahim, Ibrahim; Endi Iksan Saputra; Melsa Laela Atma; Rahma Utami (Pusat Riset dan Inovasi Nasional, 2023)
This article is entitled about the contribution of Islam in the development of world civilization. This research was conducted using two methods, namely qualitative research through questionnaires and literature studies by looking at previous studies whose theme is of course related to the title of this article. The results obtained show that Islam has made a very good contribution to world civilization, Islam has made significant contributions in various fields, including science, art, architecture, philosophy, mathematics, medicine, and many more.